Expiratory variability index (EVI) is associated with the severity of acute bronchial obstruction in small children: A proof‐of‐concept study. Issue 6 (13th May 2020) - Seppä, Ville‐Pekka; Turkalj, Mirjana; Hult, Anton; Maloča Vuljanko, Ivana; Plavec, Davor; ,; Erceg, Damir; Petković, Giorgie
Abstract: Background: Lung function testing in small children is cumbersome. However, reduced variability of tidal breathing recorded using impedance pneumography (IP) during sleep was recently found to be a potential objective marker of wheeze in children aged 1‐5 years. We aimed to investigate how an acute bronchial obstruction (BO) and its severity, and recovery thereof reflect in expiratory variability index (EVI). Methods: EVI was measured using a wearable IP system (Ventica®) during sleep in 40 healthy controls (aged 1.5‐5.9 years) and 30 patients hospitalized due to acute BO (aged 1.3‐5.3 years). In healthy controls, EVI was measured for 1‐3 nights at their homes. Patients were measured for several nights during hospitalization, as practically feasible, and at home 2 and 4 weeks post‐discharge. Results: We received 79 EVI results from 39 controls and 139 from 30 patients. 90% had previous BO episodes, 30% used asthma controller medication before and 100% after hospitalization. Compared to controls, EVI was significantly lower during hospitalization ( P  < .0001) having significant correlation with number of days to discharge ( r  = −.38, P  = .004). At 2 or 4 weeks post‐discharge, EVI was not significantly different from the controls ( P  = .14, P  = .49, respectively). EVI was significantly associated with chest auscultation findings ( P  = .0001) being 17.5 (4.9) (median, IQR) with normal auscultation, 15.6 (7.4) in those with prolonged expiration and 11.4 (6.8) in those with wheeze and/or rales and crackles. Conclusions: EVI was found to be a sensitive, objective marker of acute BO, showing strong association with changes in clinical status in wheezy children aged 1‐5 years.